Analisis Kinerja Keuangan PT Bank Muamalat Indonesia Tbk Menggunakan Metode Camel Periode 2014-2024 - Dimas Dwi Pamungkas; Hestu Nugroho Warasto (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to analyze the financial health level of PT Bank Muamalat Indonesia Tbk during the 2014–2024 period using the CAMEL method, which includes the aspects of Capital, Asset Quality, Earnings, and Liquidity. The research employed a quantitative descriptive approach utilizing secondary data derived from the published annual financial statements of PT Bank Muamalat Indonesia Tbk throughout the research period. The analysis was conducted by calculating financial ratios based on the CAMEL method and assessing the bank’s health level using the composite CAMEL score. The results indicate that the financial health of PT Bank Muamalat Indonesia Tbk was categorized as less healthy during 2014–2015, improved to moderately healthy in 2016, and experienced pressure again during 2017–2020. However, from 2021 to 2023, the bank showed significant improvement and was classified as moderately healthy. The improvement in financial health was primarily supported by strengthened capital and improved asset quality, which contributed significantly to the CAMEL score. Meanwhile, the Earnings aspect remained the main weakness due to the bank’s limited ability to generate profits, although its liquidity condition remained very strong. Overall, the CAMEL method proved effective in providing a comprehensive assessment of the financial health and stability of PT Bank Muamalat Indonesia Tbk during the research period